The pathways to health care a comparison between psychotic illness and epilepsy - Yasin, Mohd Azhar Mohd (2006)
INTRODUCTION: Identifying the pathways which patients take to reach health care is in1portant, as patients' experience of the first pathway to care n1ay determine their future compliance and progression of the illness. Understanding the type of pathways, hhich patients take and the associated factors that influence the selection are crucial infonnation for future intervention to irnprove the quality of health care. Studies on patlnvays to C'.!rc were sparse and patlnvays to care an1ong local psychiatric patients had not been explored. A Irv1: The airn of the study \Vas to describe the patlnvays to health care of psychotic patients (schizophrenia and schizophreniforn1 disorder) to the tertiary health center (psychiatry and n1edical specialized clinics in HUSM); and to cxatnine the dctnographic, social, clinical and other fl1ctors influencing the patln\'ay to care. Sin1ilar assessrnents \vere done in epilepsy patients for con1parison. f\1ETHOD: The nun1ber and type of previous healers (n1odern and traditional) visited by patients since onset of illness were assessed using nntltiplc sources of infonnation in 60 psychotic (schizophrenia and schizophrenifonn disorder) and 60 epileptic patients attending the respecti\·e specialist clinics for the first tin1e during the study period. The pathways taken by the patients before reaching the clinics were explored by using scnlistructured interview questionnaires and char1ed on a con1n1on diagram. Patients' sociodernographic data, details of the illness, and infonnation regarding the decision tnakers were also gathered during the interview from patients, and family members CONCLUSION: Epileptic and psychotic illness such as schizophrenia and schizophrcnifonn disorder have a slight different pathway in help seeking behavior. Asignificant higher nurnber of psychotic than epileptic patients consulted traditional/alternative healers. As a con1plen1entary treatrnent in Malay society, bon1oh is n1ore popular than the well-established alternative n1edicine in treating such illness. The author concluded that the study of path\vay to health care could provide a framework for better understanding of health services utilization and the associated factors that affect the services utilization. The effects of socio-cultural belief on the studied population were not - much different as con1pared to the findings fron1 the earlier studies. f Icnce there is a need for further understanding about traditional, con1plernentary and alternative medicine and collaboration between traditional/alternative and modern health services.